HERMENEUTIKA LABA PADA NELAYAN PAJEKO KELURAHAN RUA DI KOTA TERNATE - Wisudawan, Kautsar (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2024)
The aim of this research is to explore the meaning of profit and profit determination in the views of Pajeko ship owners and fishermen and to analyze and construct the meaning of profit and profit determination for Pajeko ship owners and fishermen. This research site was carried out in one of the sub-districts in the city of Ternate, namely in the Rua sub-district, Ternate Island District. The informants in this research were business actors, including ship owners, ship captains and Pajeko crew members in Rua sub-district. The research method uses descriptive research methods with a hermeneutic approach, which is a branch of philosophy as an effort to interpret texts in order to gain an understanding.The results of the research show that Pajeko boat owners and fishermen interpret profit in terms of material profit, comfort profit and security profit. Based on Hermeneutics, Intentionalism, this section explains it by grouping it into historical and cultural or cultural contexts. The meaning of profit as material profit is interpreted as the influence of historical context. The meaning of profit as a sense of comfort is interpreted as the influence of historical context and cultural or cultural context, as well as the meaning of profit as a sense of security.